Advanced carbon as emerging energy materials in lithium batteries: A theoretical perspective - Legeng Yu; Xiang Chen; Nan Yao; Yu‐Chen Gao; Yu‐Hang Yuan; Yan‐Bin Gao; Cheng Tang; Qiang Zhang (InfoMat)
Abstract Lithium batteries are becoming increasingly vital thanks to electric vehicles and large‐scale energy storage. Carbon materials have been applied in battery cathode, anode, electrolyte, and separator to enhance the electrochemical performance of rechargeable lithium batteries. Their functions cover lithium storage, electrochemical catalysis, electrode protection, charge conduction, and so on. To rationally implement carbon materials, their properties and interactions with other battery materials have been probed by theoretical models, namely density functional theory and molecular dynamics. This review summarizes the use of theoretical models to guide the employment of carbon materials in advanced lithium batteries, providing critical information difficult or impossible to obtain from experiments, including lithiophilicity, energy barriers, coordination structures, and species distribution at interfaces. Carbon materials under discussion include zero‐dimensional fullerenes and capsules, one‐dimensional nanotubes and nanoribbons, two‐dimensional graphene, and three‐dimensional graphite and amorphous carbon, as well as their derivatives. Their electronic conductivities are explored, followed by applications in cathode and anode performance. While the role of theoretical models is emphasized, experimental data are also touched upon to clarify background information and show the effectiveness of strategies. Evidently, carbon materials prove promising in achieving superior energy density, rate performance, and cycle life, especially when informed by theoretical endeavors.